T2-Imaging Changes in the Nigrosome-1 Relate to Clinical Measures of Parkinson’s Disease - Fu, Katherine A.; Nathan, Romil; Dinov, Ivo D.; Li, Junning; Toga, Arthur W. (Frontiers in Neurology, 2016)
Background: The nigrosome-1 region of the substantia nigra (SN) undergoes the greatest and earliest dopaminergic neuron loss in Parkinson’s disease (PD). As T2-weighted MRI scans are often collected with routine clinical MRI protocols, this investigation aims to determine whether T2-imaging changes in the nigrosome-1 are related to clinical measures of PD and to assess their potential as a more clinically accessible biomarker for PD. Methods: Voxel intensity ratios were calculated for T2-weighted MRI scans from 47 subjects from the Parkinson’s Progression Markers Initiative (PPMI) database. Three approaches were used to delineate the SN and nigrosome-1: 1) manual segmentation, 2) automated segmentation and 3) area voxel-based morphometry. Voxel intensity ratios were calculated from voxel intensity values taken from the nigrosome-1 and two areas of the remaining SN. Linear regression analyses were conducted relating voxel intensity ratios with the Movement Disorder Society-Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) sub-scores for each subject. Results: For manual segmentation, linear regression tests consistently identified the voxel-intensity ratio derived from the dorsolateral SN and nigrosome-1 (IR2) as predictive of nBehav (p= 0.0377) and nExp (p= 0.03856). For automated segmentation, linear regression tests identified IR2 as predictive of Subscore IA (nBehav) (p= 0.01134), Subscore IB (nExp) (p= 0.00336), Score II (mExp) (p= 0.02125) and Score III (mSign) (p= 0.008139). For the voxel-based morphometric approach, univariate simple linear regression analysis identified IR2 as yielding significant results for nBehav (p = 0.003102), mExp (p = 0.0172), and mSign (p = 0.00393). Conclusions: Neuroimaging biomarkers may be used as a proxy of changes in the nigrosome-1, measured by MDS-UPDRS scores as an indicator of the severity of PD. The voxel-intensity ratio derived from the dorsolateral SN and nigrosome-1 was consistently predictive of non-motor complex behaviors in all three analyses and predictive of non-motor experiences of daily living, motor experiences of daily living, and motor signs of PD in two of the three analyses. These results suggest that T2- changes in the nigrosome-1 may relate to certain clinical measures of PD. T2-changes in the nigrosome-1 may be considered when developing a more accessible clinical diagnostic tool for patients with suspected PD.